2015
DOI: 10.1134/s0006297915080106
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics investigation of a mechanism of allosteric signal transmission in ribosomes

Abstract: The ribosome is a molecular machine that synthesizes all cellular proteins via translation of genetic information encoded in polynucleotide chain of messenger RNA. Transition between different stages of the ribosome working cycle is strictly coordinated by changes in structure and mutual position both of subunits of the ribosome and its ligands. Therein, information regarding structural transformations is transmitted between functional centers of the ribosome through specific signals. Usually, functional cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 63 publications
2
11
0
Order By: Relevance
“…Viewing ribosomal protein extensions as connecting wires that play a role in information transfer is consistent with experimental data showing that RNA 21 22 and some proteins 23 24 25 participate in allosteric coordination and information exchange between distant parts of the ribosome. In addition, our study provides new structural insights to decipher the molecular mechanisms of allosteric communication within disordered proteins 26 27 .…”
Section: Resultssupporting
confidence: 81%
“…Viewing ribosomal protein extensions as connecting wires that play a role in information transfer is consistent with experimental data showing that RNA 21 22 and some proteins 23 24 25 participate in allosteric coordination and information exchange between distant parts of the ribosome. In addition, our study provides new structural insights to decipher the molecular mechanisms of allosteric communication within disordered proteins 26 27 .…”
Section: Resultssupporting
confidence: 81%
“…Therefore A2062 seems to be perfectly located to sense the nascent polypeptide chain and communicate the stalling signal to the PTC. The crucial role of A2503 and A2062 for signal transmission was also emphasized by molecular dynamics simulations (41). A2062 is universally conserved and highly flexible (42).…”
Section: Discussionmentioning
confidence: 99%
“…A recent computational analysis of conserved contacts between ribosomal protein extensions revealed protein-based circuits analogous to neural networks organized along the path of tRNA translocation, and around the peptide exit tunnel (78). Classical genetic studies, in which networks are identified by their disruption upon mutation of key interacting elements located both in ribosomal proteins and rRNAs, have been critical in identifying many of the rRNA-based allosteric information exchange networks revealed here (32,33,5355,57,67,70,71,7982). …”
Section: Discussionmentioning
confidence: 99%